Is Kantian ethics left defenseless in the face of evil? - Matthew Stapleton (Ethic@: an International Journal for Moral Philosophy)
Within this essay the question of whether Kantian ethics is left defenseless in the face of evil is unfolded. Some thinkers claim that it is not advisable to rigorously adhere to the categorical imperative. That is to say, it is prudent only to follow the categorical imperative, acting in such a way that you may will that the maxim of your actions becomes a universal law, when one is dealing with other ethical beings. However, when dealing with evil, it is claimed that we should develop other special principles that allow for consequences favorable to the ethical party. This essay takes exception with this claim, demonstrating that for Kant such a problem would not have even appeared. Furthermore, this essay argues that to deviate from the moral principle does damage to the truth and humanity as a whole.